1939
DOI: 10.1055/s-0028-1120360
|View full text |Cite
|
Sign up to set email alerts
|

Über die Ausbreitung und Absorption des Ultraschalls im menschlichen Gewebe und seine therapeutische Wirkung an Ischias und Plexusneuralgie

Abstract: Über die Einwirkung von LTltraschallstrahlung auf lebende Organismen, im besonderen einzellige Lebewesen, Blutkörperchen, Protoplasma usw., sind eine Anzahl von Untersuchungen veröffentlicht worden (1). Es handelt sich beim Ultraschall (US.) um Schall von so hoher Frequenz, daß er für das menschliche Ohr nicht mehr wahrnehmbar ist, infolge seiner hohen Frequenz und geringen Wellenlänge läßt er sich verhältnismäßig scharf bündeln, sodaß von US.-Strahlen gesprochen werden kann. Außerdem vermag man ihn in einer I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

1979
1979
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 0 publications
0
17
0
4
Order By: Relevance
“…Although this dose of ultrasound treatment creates some increase in heat, it did not cause any kind of thermal injury. 2,3 The first official report of a diagnostic application of ultrasound was published in 1942 by Dussik,4 a neurologist at the University of Vienna. He used ultrasound beams transmitted through the head to locate brain tumors and cerebral ventricles.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Although this dose of ultrasound treatment creates some increase in heat, it did not cause any kind of thermal injury. 2,3 The first official report of a diagnostic application of ultrasound was published in 1942 by Dussik,4 a neurologist at the University of Vienna. He used ultrasound beams transmitted through the head to locate brain tumors and cerebral ventricles.…”
Section: Historical Perspectivementioning
confidence: 99%
“…The ability of ultrasound to heat tissues has been known and utilized for many years (Freundlich et al, 1932;Pohlman et al, 1939;Bergmann 1954). * Ultrasound in the frequency range 0.5-5 MHz has widespread uses as a therapeutic agent in physical medicine (Summer and Patrick, 1964;Wells, 1977).…”
Section: Ultrasoundmentioning
confidence: 99%
“…Some reports contain inadequacies in the dosimetry and/or experimental arrangements related to the ultrasound exposures. Only ten (Sanada et al 1977, Scheidt et al 1978, Lyons 1980, Testart et al 1982, Moore et al 1982, Bause et al 1983, Stark et al 1983, and Hamilton et al 1984, Wilson and Waterhouse 1984, and Diamond 1985 of the reported investigations in this tabulation are associated with in situ clinical diagnostic exposures on human and five (Pohlman et al 1939, Bierman 1954, Paaske et al 1973, Dyson et al 1976, and Bekhome 1977 with human physical therapy exposures. These are tabulated in the appropriate category so they can be reviewed in context with data from animal investigations.…”
mentioning
confidence: 91%